Aplikasi Zeolit Sebagai Adsorben Untuk Menyisihkan Logam Fe Pada Air Gambut - Maya Septiani Wijaya; Lita Darmayanti; Shinta Elistya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Zeolites are crystalline aluminosilicate minerals with a three-dimensional open structure containing pores that can occupied by water and by alkali and alkaline earth cations. Zeolite can be used as an adsorbent in water treatment, one of which is as an adsorbent in peat water treatment. The adsorption process uses absorbents to absorb Fe in peat water. The purpose of this study is to determine the effect of mass ratio of zeolite with variation of mass 1; 1,.5; 2; 2,5; 3; 3,5 and 4 gr. The highest removal efficiency 96,33 % was reached by the zeolite with 2,5 gr of mass. Keywords: Zeolite, Adsorbent, Fe, Peat water